"Pojoča cerkev v samoti" - Šter, Katarina (De musica disserenda, 2007)
In all its long history, the Carthusian Order has never been reformed and has always remained true to the principles of the Consuetudines (Customs), written by the Order's fifth prior, Guigo. The article discusses the history of the Order and some characteristics of the Carthusian liturgy to discover, finally, the role and meaning of its liturgical music - which has remainded Gregorian chant up to the present day.
Keywords: Carthusians; kartuzijani; liturgija; gregorijanski koral